Responses of the arcto-boreal krill species Thysanoessa inermis to variations in water temperature: coupling Hsp70 isoform expressions with metabolism - Hünerlage, Kim; Cascella, Kevin; Corre, Erwan; Toomey, Lola; Lee, Chi-Ying; Buchholz, Friedrich; Toullec, Jean-Yves (Cell Stress and Chaperones, 2016)
Recent studies have indicated a metabolic temperature sensitivity in both the arcto-boreal krill species Thysanoessa inermis and Thysanoessa raschii that may determine these species’ abundance and population persistence at lower latitudes (up to 40 degrees N). T. inermis currently dominates the krill community in the Barents Sea and in the high Arctic Kongsfjord. We aimed to increase the knowledge on the upper thermal limit found in the latter species by estimating the CT50 value (19.7 degrees C) (critical temperature at which 50 % of animals are reactive) and by linking metabolic rate measurements with molecular approaches. Optical oxygen sensors were used to measure respiration rates in steps of 2 degrees C (from 0 to 16 degrees C). To follow the temperature-mediated mechanisms of passive response, i.e., as a proxy for molecular stress, molecular chaperone heat shock protein 70 (Hsp70) sequences were extracted from a transcriptome assembly, and the gene expression kinetics were monitored during an acute temperature exposure to 6 or 10 degrees C with subsequent recovery at 4 degrees C. Our results showed upregulation of hsp70 genes, especially the structurally constitutive and mitochondrial isoforms. These findings confirmed the temperature sensitivity of T. inermis and showed that the thermal stress took place before reaching the upper temperature limit estimated by respirometry at 12 degrees C. This study provides a baseline for further investigations into the thermal tolerances of arcto-boreal Thysanoessa spp. and comparisons with other krill species under different climatic regimes, especially Antarctica.